Transfer Teknologi Pengolahan Bunga Telang (Clitoria ternatea) menjadi Teh Celup Herbal di Desa Dayang Suri Kecamatan Bunga Raya Kabupaten Siak - Perdana, Fitra; Dahliaty, Andi; Nurulita, Yuana; Fawrin, Heralda; Yanti, Selfi; Haryani, Yuli (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Butterfly pea (Clitoria ternatea) is a plant that provides various health benefits due to its pharmacologically active compounds. Nevertheless, the community’s limited knowledge and skills in utilizing and processing butterfly pea into herbal tea bags underline the importance of this community service activity. Processing butterfly pea into herbal tea serves as an effective approach to make its health benefits more accessible for daily use. This program aimed to enhance community knowledge about the health properties of butterfly pea, improve their skills in producing herbal tea bags, and encourage its development as a household-scale product with market potential, given its simple and low-cost processing method. The target beneficiaries were residents of Dayang Suri Village, Bunga Raya Subdistrict, Siak Regency with 55 participants. Program achievements were measured by determining the increased knowledge and skills in processing butterfly pea into herbal tea bags, as well as growing interest in its commercialization. Pre- and post-test results demonstrated a significant improvement in participants’ average scores from 45% to 87%, with a statistically significant paired t-test result (α=0.05).